Efectos jurídicos y sociales generados por la eliminación del aporte estatal del 40% al Instituto Ecuatoriano De Seguridad Social - Orellana Angueta, Franklin Rene (2016)
The legal research plan that arises is related to a social and legal conflict scenario is evident in relations between the state and subject to social security in Ecuador; having as background the effect that caused the force of the Organic Law of Labor Justice and Labor Award at Home, published on April 20, 2015 in the Official Gazette, Third Supplement, No. 483, in the main legislation reform the Social Security Act, the law of public enterprises, the organic law of public service and the labor code. From a critical perspective, the reforms enacted require serious analysis to determine profits and losses have begun to generate in the future and generate the aforementioned regulatory changes, being an unavoidable obligation as a professional future of law, challenge constructively deficiencies structural perceived in this law, and in this case as my task, identify the array problem in my opinion is the elimination of the 40% state contribution for the payment of retirement pensions, which has caused an upset social because of the negative effect caused when the rules in question eliminates the donation. In this case, it should be incorporated into the General State Budget respective resources, even on other expenses." Another effect was caused ignorance of the payment obligations via payment agreements were signed by officials of the current system of government, as well as the reports of the Comptroller General of the state, the state in which commitments were determined with the IESS. With the introductory approach made, I am able to make some considerations that will be the basis of my study, because in effect the removal of the government contribution of 40% of the Ecuadorian Social Security Institute (IESS) for retirement pensions enters divergence instruments international human rights treaties ratified by Ecuador, resulting in an impairment of the constitutional framework, then remember that the constituent reflected in the current Constitution that will any unconstitutional act or omission that diminishes regressive, or unjustifiably impair defeat the exercise of rights. With the above exposed premise is essential to generate proposals to solve the problem focused, and precisely in this way, I consider it necessary to review the regulatory framework has incorporated reforms to social security, to identify limitations in form and substance and from Here, promote improved conditions and care to beneficiaries of the social security system by articulated management services provided by the Ecuadorian Institute of Social Security and the strengthening of strategic planning processes in this area, to achieve actual compliance institutional goals and objectives of management and customer service in line with the standards of quality, efficiency and existing in other states and societies in the field of social security efficiency.